ENERGY DISSIPATION OF ECCENTRICALLY-BRACED-FRAME (EBF) WITH DIFFERENT LEVEL OF ECCENTRICITY - Pah, Jusuf J. S.; Oematan, Yanes E. (Jurnal Teknik Sipil, 2012)
ABSTRACTThis research aimed at eliciting the form of relation that exists between level ofeccentricity (e/L) and energy dissipation (Ed) of an Eccentrically Braced Frame (EBF).It continued a previous research that studied relative stiffness of an EBF. Three sets ofEBF specimen were analysed by the merit of SAP2000 v9.0.1 computer-software toobtain range of inelastic drifts and its corresponding range of lateral loads. Specimensvary in level of eccentricity (e/L) and bay to height ration (h/L). Prior to it, a formulathat calculates energy dissipation of a lateral resistant structure as product of lateralloads and the corresponding drifts was developed and used throughout the research forthe purpose of quantifying Ed. Each specimen was alternatively loaded in directionconfronting and concurring the bracing component. It was found that there was nosignificant difference in the form of relation between e/L and Ed, when lateral loadapplied confronting bracing component from when the same load applied concurringbracing component. Forms of each graph that relates e/L to Ed was presented andshown to consists of two parts, divided at e/L = 0.2; suggesting that e/L = 0.2 might bethe point where level of eccentricity and relative stiffness of an EBF reach optimum.Mathematical equations for the relation between e/L and Ed of an EBF were thendeveloped. In spite of this, an inconsistency with the prevalent theory was observed,hence the relations between e/L and Ed concluded so far were contested until furtherresearches be made for clarification.